(untitled) (Nepal Medical College Journal, 2025)
The knee joint is the bicondylar variety of synovial joint of the human body formed by the articulation of lower end of femur with the tibia and patella. The anterior cruciate ligament (ACL) is an intra-articular, extra synovial ligament which is most frequently damaged ligament and also requires reconstructive surgery. As there are variation among the age, gender and different populations, the morphometric understanding of ACL is essential. This study aimed to assess the morphometric analysis of ACL in a cadaver. A descriptive observational study was carried out in the Department of Human Anatomy, Nepal Medical College and Teaching Hospital from August 2024 to July 2025 in 26 cadavers including both right and left knees. The formalin preserved cadaveric knees were dissected, exposing the knee joint following the standard procedures. The length and breadth of the ACL were measured by Digital Vernier Caliper. The mean and standard deviation was calculated applying SPSS version 16. All the 52 knees were measured and the mean length of ACL was 38.5 ± 0.49 mm and mean breadth of ACL was 10.00 ± 0.19 mm. The mean length of right and left side ACL was 38.60 ± 0.47 mm. and 38.40 ± 0.52 mm respectively. Similarly, the mean breadth of right and left side of ACL was 9.70 ± 0.16 mm and 10.31 ± 0.22 mm respectively. The present study concluded that the variation in both length and breadth of right and left ACL exists. A thorough understanding of ACL is mandatory during surgical intervention and reconstructive procedure of anterior cruciate ligament.